Historical Patterns of Diagnosis, Treatments, and Outcome of Epilepsy Associated With Tuberous Sclerosis Complex: Results From TOSCA Registry - Nabbout, Rima; Belousova, Elena; Benedik, Mirjana P.; Carter, Tom; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D'Amato, Lisa; Beaure d'Augères, Guillaume; de Vries, Petrus J.; Ferreira, José C.; Feucht, Martha; et al. (Frontiers in Neurology, 2021)
Background: Epilepsy is the most common neurological manifestation in individuals with tuberous sclerosis complex (TSC). However, real-world evidence on diagnosis and treatment patterns is limited. Here, we present data from TuberOus Sclerosis registry to increase disease Awareness (TOSCA) on changes in patterns of epilepsy diagnosis, treatments, and outcomes over time, and detailed epilepsy characteristics from the epilepsy substudy. Methods: TuberOus Sclerosis registry to increase disease Awareness (TOSCA) was a multicentre, international disease registry, consisting of a main study that collected data on overall diagnostic characteristics and associated clinical features, and six substudies focusing on specific TSC manifestations. The epilepsy substudy investigated detailed epilepsy characteristics and their correlation to genotype and intelligence quotient (IQ). Results: Epilepsy was reported in 85% of participants, more commonly in younger individuals (67.8% in 1970s to 91.8% in last decade), while rate of treatments was similar across ages (>93% for both infantile spasms and focal seizures, except prior to 1960). Vigabatrin (VGB) was the most commonly used antiepileptic drugs (AEDs). Individuals with infantile spasms showed a higher treatment response over time with lower usage of steroids. Individuals with focal seizures reported similar rates of drug resistance (32.5–43.3%). Use of vagus nerve stimulation (VNS), ketogenic diet, and surgery remained low. Discussion: The epilepsy substudy included 162 individuals from nine countries. At epilepsy onset, most individuals with infantile spasms (73.2%) and focal seizures (74.5%) received monotherapies. Vigabatrin was first-line treatment in 45% of individuals with infantile spasms. Changes in initial AEDs were commonly reported due to inadequate efficacy. TSC1 mutations were associated with less severe epilepsy phenotypes and more individuals with normal IQ. In individuals with TSC diagnosis before seizure onset, electroencephalogram (EEG) was performed prior to seizures in only 12.5 and 25% of subsequent infantile spasms and focal seizures, respectively. Conclusions: Our study confirms the high prevalence of epilepsy in TSC individuals and less severe phenotypes with TSC1 mutations. Vigabatrin improved the outcome of infantile spasms and should be used as first-line treatment. There is, however, still a need for improving therapies in focal seizures. Electroencephalogram follow-up prior to seizure-onset should be promoted for all infants with TSC in order to facilitate preventive or early treatment.